Clinical diagnostic approach in the treatment of chronic periodontitis in mandibular molars: Clinical cases - M. A. Postnikov; A. M. Golovachev; S. E. Chigarina; D. N. Kudryashov; I. A. Zakharova; S. A. Burakshaev (Кубанский научный медицинский вестник, 2023)
Background. Inflammatory process in periapical tissues causes tooth extraction in more than 50% of cases. The development of chronic apical periodontitis can be triggered by an intracanal infection in undetected/missed root canal of the mandibular molars. The morphology of mandibular molars is distinguished by additional canals in the mesial root in some cases. Different studies reveal the middle mesial canal in 4.5% to 26% of cases with quite high incidence in youth. The dental therapy has been searching for effective approaches to diagnosis and treatment of chronic periodontitis, enabling the focus of chronic inflammation to be eliminated and the tooth to be saved. Case descriptions. The paper presents clinical cases of patients with destructive changes in bone tissues in the periapical region of the mesial root in mandibular molars. The developing of this pathology is associated with missed anatomy in the mesial root during primary endodontic treatment. The patients underwent clinical examination consisting of basic methods (interview, examination) and additional techniques (intraoral radiography). An additional middle mesial canal in the root of the mandibular molar was identified taking into account the complex morphology of the root system of the tooth and verified by its careful analysis and radiography. The final clinical diagnosis, chronic apical periodontitis (K04.5), was made following the obtained diagnostic results and the ICD-10 classification. Diagnostic examination and endodontic retreatment were performed using a dental operating microscope. Conclusion. An operating dental microscope provides visualization of microscopic anatomotopographical details, promoting the efficiency of diagnosis and treatment of chronic apical periodontitis in mandibular molars. Using dental microscope facilitates systematization of the data obtained during the examination, making a final clinical diagnosis, and development of a reasonable personalized treatment plan focused on detecting an additional middle canal in the mesio-buccal canal of the mandibular molar. Due to the suggested approach, the long-term outcomes of endodontic treatment can be an objective assessed in dynamics, thereby improving the quality of treatment for chronic apical periodontitis in patients.